Cykl koniunkturalny w Turcji w latach 2005–2020 — interpretacja austriackiej szkoły ekonomii - Guzikowska, Patrycja (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
Turkey was hit by the recession, defined in a classic way (as negative real GDP growth lasting at least two quarters), three times over the discussed period. The main goal of the central bank of Turkey is to keep inflation as close as possible to the inflation target. The use of the interest rate as a tool to stabilize the economic situation is therefore limited. The country has experienced periods of high inflation which was not temporary, but long-term. Using the approach appropriate to the Austrian School of Economics, the article analyzes the behavior of the Turkish economy in 2005–2020. In the discussed time horizon, two phases of the business cycle have been identified according to the Austrian School of Economics — the first from 2005 to the first quarter of 2014, and the second from the second quarter of 2014 to 2020. It can be assumed that the Turkish economy will enter the third phase of the business cycle in the near future, although it is difficult to determine whenit will happen.
Keywords: Turkey; business cycle; Austrian School of Economics